1981
DOI: 10.1113/jphysiol.1981.sp013787
|View full text |Cite
|
Sign up to set email alerts
|

The neuromuscular junction of the mouse after black widow spider venom.

Abstract: 6. These findings show that the re-innervation oforiginal end-plates is ofimportance in facilitating the rapid return oftransmission to normal levels and limiting the extent of axonal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Morphological analy-sis of NMJs exposed to CGM3 reveals extensive deposits of anti-disialosyl antibody and complement products, localized to both the nerve terminal and the overlying perisynaptic Schwann cells (pSCs) Halstead et al, 2004). At physiological extracellular calcium concentrations, there is a severe loss of cytoskeletal proteins that can be attenuated by calpain inhibition (O'Hanlon et al, 2003), accompanied by major physical disruption of the terminal axon, including vesicle depletion and complete separation of the axon from the postsynaptic membrane, i.e., denervation (Duchen et al, 1981;Willison and O'Hanlon, 1999;O'Hanlon et al, 2001). Using nuclear ethidium homodimer (EthD-1) uptake as an index of disrupted plasma membrane permeability (by MAC pores) and cell death (Reddy et al, 2003;Halstead et al, 2004), we have also observed concurrent pSC death at a high proportion of NMJs (Halstead et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Morphological analy-sis of NMJs exposed to CGM3 reveals extensive deposits of anti-disialosyl antibody and complement products, localized to both the nerve terminal and the overlying perisynaptic Schwann cells (pSCs) Halstead et al, 2004). At physiological extracellular calcium concentrations, there is a severe loss of cytoskeletal proteins that can be attenuated by calpain inhibition (O'Hanlon et al, 2003), accompanied by major physical disruption of the terminal axon, including vesicle depletion and complete separation of the axon from the postsynaptic membrane, i.e., denervation (Duchen et al, 1981;Willison and O'Hanlon, 1999;O'Hanlon et al, 2001). Using nuclear ethidium homodimer (EthD-1) uptake as an index of disrupted plasma membrane permeability (by MAC pores) and cell death (Reddy et al, 2003;Halstead et al, 2004), we have also observed concurrent pSC death at a high proportion of NMJs (Halstead et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Such paralysis is completely reversible, and within a month or so, patients, supported by mechanical ventilation, recover completely (1)(2)(3). Paralysis in mice/rodents has a shorter duration, and again recovery is complete (4,5). Major presynaptic toxins of these venoms are α-latrotoxin (α-Ltx), taipoxin (Tpx), and β-bungarotoxin (β-Btx), respectively (6,7).…”
mentioning
confidence: 99%
“…Indeed, these neurotoxins cause activation of the calcium-activated calpains that contribute to cytoskeleton fragmentation (22). Although clearly documented (4,5,20), the regeneration of the motor axon terminals after presynaptic neurotoxins injection is poorly known in its cellular and molecular aspects. Available evidence indicates that, in general, regeneration of mechanically damaged motor neuron terminals relies on all three cellular components of the neuromuscular junction (NMJ): the neuron, the perisynaptic Schwann cells (PSCs), and the muscle cells (23,24).…”
mentioning
confidence: 99%
“…An increase in nodal axoplasmic volume might be expected to result from the influx of sodium ions and the consequent rise in intra-axonal osmotic pressure (Hill, 1950). The osmotic gradient would be markedly increased by agents such as Leiurus venom, which may prolong the duration of sodium influx (and hence of depolarization) for many seconds (Adam, Schmidt, Stiimpfli & Weiss, 1966 (Duchen, Gomez & Queiroz, 1981;Queiroz & Duchen, 1982). Unlike these, Phoneutria venom does not lead to widespread degeneration of intrafusal and extrafusal nerve terminals.…”
Section: Discussionmentioning
confidence: 99%